The dynamics of the linguistic system : usage, conventionalization, and entrenchment - Schmid, Hans-Jörg, 1963- (Oxford University Press, 2020)
This volume outlines a model of language that can be characterized as functionalist, usage-based, dynamic, and complex-adaptive. The core idea is that linguistic structure is not stable and uniform, but continually refreshed by the interaction between three components: usage, the communicative activities of speakers; conventionalization, the social processes triggered by these activities and feeding back into them; and entrenchment, the individual cognitive processes that are also linked to these activities in a feedback loop. Hans-Joerg Schmid explains how this multiple feedback system works by extending his Entrenchment-and-Conventionalization Model, showing how the linguistic system is created, sustained, and continually adapted by the ongoing interaction between usage, conventionalization, and entrenchment. Fulfilling the promise of usage-based accounts, the model explains how exactly usage is transformed into collective and individual grammar and how these two grammars in turn feed back into usage.0The book is exceptionally broad in scope, with insights from a wide range of linguistic subdisciplines. It provides a coherent account of the role of multiple factors that influence language structure, variation, and change, including frequency, economy, identity, multilingualism, and language contact.
Keywords: jazyk; lingvistika; sociolingvistika; language; linguistics; sociolinguistics; monografie; monographs